Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar Tematik Siswa Materi Peduli Terhadap Makhluk Hidup di Kelas IV UPT SD Negeri 066667 Medan Denai - P, Sulisti Khairani; Nurmairina, Nurmairina (Indonesian Research Journal on Education, 2022)
Based on the observations of fourth grade students at SDN 066667 Medan Denai, student learning outcomes are still categorized as low. This is caused by several factors, students have difficulty in understanding the learning material delivered by the teacher because learning is still centered on the teacher. Based on this, an effort is needed to encourage students to be directly involved in doing their work while solving problems in learning. By applying the Problem Based Learning model. This research method uses Classroom Action Research (CAR). The subjects of this study were all fourth grade students at SDN 066667 Medan Denai for the academic year 2021/2022 which consisted of 17 students. The instruments used in this study were teacher activity observation sheets, student activity observation sheets, and student learning outcomes sheets. Then this data was analyzed using the percentage formula. Based on the results of data analysis, the teacher's activity in the first cycle scored an average of 71.76% in the good category and increased in the second cycle the score was 94.11% in the very good category. Meanwhile, student activity in the first cycle scored 70% in the good category, and increased in the second cycle to get a score of 92.5% in the very good category. From the management of the level of student learning outcomes in the first cycle, the score was 61.76% in the sufficient category and increased in the second cycle to 80.29% in the very good category. Thus the Problem-Based Learning model can improve student learning outcomes in class IV SDN 066667 Medan Denai.